Noncompliance to smoke-free law: which hospitality premises are more prone? - AY, NADİYE PINAR (W B SAUNDERS CO LTD, 2016)
Objectives: In Turkey, smoking has been banned in hospitality establishments since July 2009. The objective of this study was to determine noncompliance to the smoke-free law and its change in 2 consecutive years in enclosed spaces of hospitality venues and also to evaluate the factors associated with noncompliance. Study design: This is an observational study. Methods: Hospitality venues in Istanbul were visited, and data were collected through direct observation and interviews. Observation of smoking, cigarette butts or existence of ashtrays were defined as noncompliance. The survey was repeated in 2 consecutive years; the venues were visited both in 2013 and 2014. Logistic regression was used to evaluate factors associated with noncompliance. Results: In 2013, 450 establishments were visited, and in the next year, 367 (81.6%) were revisited. Noncompliance for 2013 and 2014 were 49.0% and 29.7%, respectively. The highest violation was observed in bars and traditional coffeehouses. There was a significant decrease in noncompliance from 2013 to 2014 among restaurants and cafes, while such a change was not observed among bars and traditional coffeehouses. In the multivariate analysis, venues other than restaurants, venues that did not have no-smoking signs and venues which had been issued fines previously had increased probability of noncompliance. Conclusions: While compliance to smoke-free law had increased significantly within 1 year, almost one third of the venues were still violating the law in 2014. The venues which were issued fines continued to violate the law. There is a need to strengthen enforcement efforts and revise the methods of enforcement and penalties in hospitality establishments. (C) 2016 The Royal Society for Public Health. Published by Elsevier Ltd. All rights reserved.
Keywords: Smoke free; Compliance; Policy; Hospitality; FREE LEGISLATION; PUBLIC PLACES; TOBACCO-SMOKE; RESTAURANTS; INDIA; EXPOSURE; BARS; COUNTRIES; DISTRICT; TURKEY